A Comparison of Prices Generated by The Derivative Commodity Model (Ornstein-Uhlenbeck Process) With Those Obtained by The Conventional Arbitrage-Free Method of Pricing Forward Derivatives with Respect to Tea in Nduti Tea Factory Kenya. - MUMU, Patrick (Journal of Statistics and Actuarial Research, 2016)
Purpose: The purpose of this study was to compare the prices generated by the derivative commodity model with those obtained by the conventional arbitrage-free method of pricing forward derivatives with respect to tea. Methodology: The study used descriptive survey research design. The study used descriptive survey research design. This study used secondary data which was collected from Nduti Tea Factory website. The target population of the study were 318 auction days auction days on the stock exchange spread over from 18/12/2007 to 2/12/2014. Purposive sampling was used to select 6 working days excluding Sundays and holidays starting from 18/12/2014 to 2/12/2014.Data from the websites was analysed using the Ornstein Uhlenbeck process, to derive descriptive results. Results: The findings implied that there was variations in forward prices calculated by derivative commodity model as compared to those calculated conventional arbitrage-free. Unique contribution to theory, practice and policy: The study provides need to insuring farmers from uncertainty by ensuring they get value for the input and costs of production. On the other hand, consumers are protected from the volatile food commodity prices. An incentive for the farmer is established and hence increased and more efficient productivity is witnessed. The study will lead to designing a simple commodity derivative with different times to expiry for tea in Kenya and elsewhere based on estimated future market prices. The results of this study will be of particular significance to farmers, cooperatives and general investors.